Perbedaan Jumlah Leukosit yang Dihomogenisasi Sekunder Sebanyak 2 dan 8 Kali setelah Didiamkan Selama 30 Menit - Kartika Englishiana; Rosnita Sebayang; Mustika Sari Hutabarat (Fakultas ilmu Kesehatan Universitas Katolik Musi Charitas, 2023)
Background: Leukocytes are one of the hematological examinations. Blood collected in K2EDTA tubes must be primary homogenized and then examined. However, sometimes in the laboratory, the examination is not carried out immediately after blood collection so that if it is allowed to stand for some time, it must be secondary homogenized so that it does not form a precipitate and mixes well. Objective: To determine whether there is a difference in the number of leukocytes that are secondary homogenized 2 and 8 times after standing for 30 minutes. Methods: This type of research is a cross-sectional study. Blood was examined using the Sysmex XP- 100 tool with the impedance method in the UKMC FIKES Clinical Chemistry laboratory. The samples in this study were students from the DIV Medical Laboratory Technology Study Program level I and IV by total sampling. Data were analyzed using the Paired Samples T Test. Results: Secondary homogenized leukocyte count examination 2 times obtained an average result of 7.41 x 103 /µl, and secondary homogenized leukocyte count 8 times obtained an average result of 7.43 x 103 /µl. These results show there is no significant difference between secondary homogenization 2 and 8 times with p (sig) = 0.852 (> 0.005). Conclusion: Based on this study, it can be concluded that there is no difference in the results of secondary homogenized leukocyte counts 2 and 8 times. Suggestion: Secondary homogenization is sufficient for 2 times after the sample has been allowed to stand for 30 minutes.